Comparative foliar morphological and palynological studies of Cleomaceae of Assam, India (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Das B, Roy S, Kalita S, Boro KK, Nath M, Nath N. 2022. Comparative foliar morphological and palynological studies of Cleomaceae of Assam, India. Biodiversitas 23: 2920-2934. The Cleomaceae is a well-known angiospermic family. There is no record of extensive study on the members of the family Cleomaceae in the state of Assam. Though the species Cleome houtteana is found abundantly in the studied area, it was not reported in any of the major floristic works of the region and it was misidentified as Gynandropsis gynandra by many of the earlier workers. So, the present work was carried out to do a detailed comprehensive study on the morphology, foliar macro and micro-morphology (epidermis, stomata, and trichome), leaf venation pattern, along with palynological characters of the four species of Cleomaceae viz. Gynandropsis gynandra, Cleome houtteana, Sieruela rutidosperma, and Arivela viscosa of Assam, India. These species show similarities with each other, but can be well differentiated using the studied characters here. Detailed taxonomic descriptions have been given along with relevant information and color photographs for the correct identification of all four different species.